Communication Organic Law Commented, review - Gabriela Rodríguez Llamas (Universidad Hemisferios, 2021)
This work contains a review of the work “Organic Communication Law commented” by Dr. Juan Carlos Riofrío Martínez-Villalba, as well as a brief comment on the profound reforms made to this law made in February 2019. Some lights and shadows of this reform are shown here, following the author’s commentaries. It is also explained here how this work is part of the Ecuadorian Digest collection, that the Corporación de Estudios y Publicaciones (CEP), with the University of the Hemispheres, are taking forward. In the first part we talk about the author and about the opportunity of the work. Then, in Part II we discuss the aims of the reform. Finally, in Part III we include some conclusions that help us assess the reform and the commented work. Although what has been done to reconquer freedom of expression is very positive, following the author comments, we miss the disappearance of the principles of communication, which today only remain as doctrinal standards in our environment.